Method of Habituation Pillars Character Building Students in Covid Era - Utama, Mohamad Maulidin Alif (At-Tarbawi: Jurnal Pendidikan, Sosial dan Kebudayaan, 2022)
As of May 26, 2020, the world was shocked by a virus outbreak that spread across planet earth, the impact of which must be felt by the world community in general and the Indonesian people in particular. This virus has infected 5,623,503 people, with a death toll of 348,760 and several patients who recovered 2,393,552 and infected 213 countries, according to world meters that informed it in 2020. Therefore, the world is currently busy with the emergence of the virus. the. The virus is known as the coronavirus or Covid-19. Meanwhile, in Indonesia itself, the spread of the coronavirus was first discovered on March 2, 2020, and this was conveyed directly by President Joko Widodo. If the atmosphere of the family or home environment is not supportive, then all maturity that is ready to develop will not develop. So if the atmosphere of the family or home environment is not conducive, it will affect the formation of character in children This research uses the library research method. The Result of this research is the habituation method is the right way or system and is recommended to be used in the context of character building, especially during this pandemic because children interact more with their families than with teachers, it is an opportunity for parents to instil their children's character through habituation methods.